Thermal Annealing Effects on Naturally Contacted Monolayer MoS2. Issue 9 (15th January 2021) - Bizhani, Maryam; Thorat, Ruhi; Poston, William; Wickramasinghe, Thushan; Aleithan, Shrouq H.; Stinaff, Eric
Abstract : Transition metal dichalcogenides such as MoS2, which can be produced in monolayer form, have attracted attention because of their interesting and potentially useful electrical and optical properties. These properties often depend sensitively on material properties such as defect density and crystallinity. Herein, the effects of postgrowth annealing on monolayer MoS2 grown using a novel chemical vapor deposition process are investigated. In this process bulk molybdenum patterns serve as the nucleation site and source material for high‐quality MoS2 material growth. After postgrowth thermal annealing, the photoluminescence is found to blueshift and become more uniform up to an annealing temperature of 300 °C. At higher temperatures, isolated monolayers begin to crack along the grain boundaries, which leads to variations in luminescence, whereas after annealing temperature of 200 °C, material anchored to the molybdenum patterns is found to easily ablate. Abstract : A photoluminescence study of the effects of postgrowth thermal annealing on naturally contacted chemical vapor deposition (CVD)‐grown 2D MoS2 is presented, providing insight into the nucleation, growth mechanism, and defect properties for materials produced with this novel growth process.